2018
DOI: 10.1002/hed.25375
|View full text |Cite
|
Sign up to set email alerts
|

Transoral surgery using the Flex Robotic System: Initial experience in the United States

Abstract: Background This multicenter, retrospective review documents the initial experience using the Flex system for transoral surgery in 2 United States academic centers. Methods All patients who underwent transoral robotic surgery using the Medrobotics Flex Robotic System (Raynham, MA) between September 2015 and May 2017 were reviewed. Rates of successful surgery and complications were evaluated. Results Thirty‐six men and 32 women were enrolled in the study. The average age was 55.6 years (range 17‐82 years). The F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The daVinci® surgical robot (Intuitive Surgical® Inc, Sunnyvale, CA, USA), allowing for a magnified and three-dimensional view through a dual endoscope, tremor filter, scaling of robotic arm movements and range of movement, is hereby the most commonly used robotic system (RS). But novel platforms, such as the Flex® Robotic System (Medrobotics® Cooperation, Raynham, MA, USA) particularly addressing obstacles in the head and neck, are also becoming more popular for performing TORS [ 7 , 8 ]. Multiple large prospective studies have indicated safety and demonstrated favorable prognostic and functional outcome of TORS in treatment of patients with head and neck squamous cell carcinoma (HNSCC) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The daVinci® surgical robot (Intuitive Surgical® Inc, Sunnyvale, CA, USA), allowing for a magnified and three-dimensional view through a dual endoscope, tremor filter, scaling of robotic arm movements and range of movement, is hereby the most commonly used robotic system (RS). But novel platforms, such as the Flex® Robotic System (Medrobotics® Cooperation, Raynham, MA, USA) particularly addressing obstacles in the head and neck, are also becoming more popular for performing TORS [ 7 , 8 ]. Multiple large prospective studies have indicated safety and demonstrated favorable prognostic and functional outcome of TORS in treatment of patients with head and neck squamous cell carcinoma (HNSCC) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…After abstract screening for eligibility, 61 articles were considered eligible. Among these, we included 14 articles in qualitative synthesis after a full-text assessment [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The other 47 papers were excluded for the following reasons: studies on cadavers ( n = 15) or mannequins ( n = 1), commentaries on the Flex Robotic System without patients ( n = 7), and studies on other robotic systems ( n = 24).…”
Section: Resultsmentioning
confidence: 99%
“…Among the papers that matched the inclusion criteria, five publications were case reports [ 12 , 13 , 17 , 23 , 24 ], two were case series [ 11 , 16 ], three were retrospective studies [ 18 , 20 , 21 ], and four were prospective studies [ 14 , 15 , 19 , 22 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An additional retrospective, multi-center study in the United States similarly evaluated outcomes in patients undergoing surgery using the FLEX system between 2015 and 2017. 55 Thirty-one out of 68 patients had a resection, as opposed to biopsy. The authors demonstrated superior results in terms of hemostasis in comparison to previous TORS studies.…”
Section: Energy Delivery Via the Flex Robotic Systemmentioning
confidence: 99%